Teachers’ views on methods to increase teaching of social and emotional skills and prevent digital distraction in middle school - Haikonen, Joonas Elias (2024)
In recent years, middle school students’ academic success and well-being have been decreasing in Finland. Increasing the teaching of social and emotional skills and reducing digital distraction have the potential to address these issues. Both social and emotional skills, as well as preventing digital distraction, have been studied to support students’ academic success and well-being. This study explores Finnish teachers’ perspectives on methods to increase the teaching of social and emotional skills and prevent digital distraction in middle school education. The main research questions are related to the methods that Finnish teachers would use to increase the teaching of social and emotional skills and to prevent digital distraction in middle school education. The study used thematic interviews and thematic analysis to find out what methods teachers would use. Methods were explored separately for both social and emotional skills and digital distraction regarding the following themes: teaching in a classroom environment, Finnish curriculum and teaching content, learning outside of school, and teacher training and guidance. A total of eight teachers were interviewed to gather their views. The findings indicate that teachers identified various methods for increasing social and emotional skills, such as practicing these skills during class hours, encouraging students to engage in hobby activities, as well as providing training and guidelines on integrating these skills into teaching. For preventing digital distraction, teachers mentioned methods such as managing students’ phone use, increasing students’ social and emotional skills, holding discussions with parents, and increasing teachers’ authority. Many of the mentioned methods have also been supported by previous research. This research contributes to the understanding of teachers’ perspectives on integrating social and emotional skills into education and addressing digital distraction, providing insight on what methods could be beneficial to use in education.